How digital influencer content and characteristics influence Generation Y persuasiveness and purchase intention - Rodrigues,Maria Antónia (2024)
Abstract This paper aims to understand the effect of content and digital influencer characteristics on their persuasiveness ability and Generation Y's resulting brand attitudes and purchase intentions (Millennials). Based on a sample of 201 individuals and quantitative analysis, data was analysed using Smart PLS. The results show that the quality of the content is the characteristic with the highest impact on the influencer's persuasive power. In terms of influencer characteristics, trust is a critical determinant. The influencer's persuasiveness is essential for developing a positive attitude towards the brand and purchase intention. Our findings update previous studies, focusing on Generation Y and including trust as a variable while simultaneously revealing a fundamental determinant of influence power. For brands, this study confirms the importance of having digital influencers in their strategies. For influencers, it suggests that when targeting Generation Y, they should invest in the quality of their publications and increase trust, as this is strongly linked to their persuasiveness and, consequently, to the purchase intention of their followers.